Association of pre‐pregnancy BMI and postpartum weight retention with postpartum HbA1c among women with Type 1 diabetes. Issue 2 (19th November 2014) - Huang, T.; Brown, F. M.; Curran, A.; James‐Todd, T.
Abstract Aim To examine the association of pre‐pregnancy BMI and postpartum weight retention with postpartum HbA1c levels in women with Type 1 diabetes. Methods We longitudinally evaluated 136 women with Type 1 diabetes who received prenatal, pregnancy, and postpartum care through Joslin Diabetes Center's Diabetes and Pregnancy Program between 2004 and 2009. Weight, BMI and HbA1c concentrations were assessed before the index pregnancy and repeatedly monitored after delivery until 12 months postpartum. We used linear mixed models to assess the association of postpartum HbA1c with pre‐pregnancy BMI and postpartum weight retention. Results The mean HbA1c concentration increased from 49 mmol/mol (6.6%) at 6 weeks postpartum to 58 mmol/mol (7.5%) by 10 months postpartum, a level similar to the mean pre‐pregnancy HbA1c concentration. Postpartum weight retention showed a linearly decreasing trend of 0.06 kg/week (P < 0.0001), with −0.1 kg average postpartum weight retention by 1 year postpartum. Compared with women with a pre‐pregnancy BMI ≥ 25 kg/m2, women with a lower pre‐pregnancy BMI maintained a 3.4 mmol/mol (0.31%) lower HbA1c concentration, after adjusting for several sociodemographic, reproductive and diabetes‐related factors (P = 0.03). There was a suggestion of a time‐varying positive association between HbA1c and postpartum weight retention, with the most significant difference of 3.7 mmol/mol (0.34%; P = 0.05) at 30 weeks postpartum among women with postpartum weight retention ≥ 5 kg vs those with postpartum weight retention < 5 kg. Conclusions Pre‐pregnancy BMI and postpartum weight retention were positively associated with HbA1c during the first postpartum year in women with Type 1 diabetes. Interventions to modify the behaviours associated with these body weight factors before pregnancy and after delivery may help women with Type 1 diabetes maintain good glycaemic control after pregnancy.